The Preschool Physical Literacy Assessment Tool: Testing a New Physical Literacy Tool for the Early Years - Cairney, John; Clark, Heather J.; James, Maeghan E.; Mitchell, Drew; Dudley, Dean A.; Kriellaars, Dean (Frontiers in Pediatrics, 2018)
Background: Physical literacy is essential to physical activity across the lifespan. While there is an emerging body of research on physical literacy in school-aged children, the preschool years have largely been ignored. We tested the psychometric properties of new tool, the Preschool Physical Literacy Assessment Tool (Pre-PLAY) designed to address this gap. Methods: We recruted 78 children (aged 19 to 49 months) across 5 childcare centers in Hamilton, Ontario. Two Early Childhood Educators (ECE) completed the Pre-PLAY for each child at two points in time to assess inter-rater reliability and test-retest reliability. We assessed the agreement between the Pre-PLAY tool with gross motor skills and the ability of the PPLAy to predict physical activity. Results: Results indicated Pre-PLAY is related to gross motor skills and predictive of physical activity for females, but not males. Inter-rater and intra-rater reliability was at least adequate for all but the co-orindated movements items and scale for females, but ECEs showed poor agreement for males. Conclusions: These results suggest initial support for the Pre-PLAY tool as a measure of physical literacy during the early years. However, some modification to the items and training are required to address the gender-specific effects found in this sample.